HUBUNGAN ASUPAN ZAT GIZI DENGAN KEJADIAN ANEMIA PADA IBU HAMIL TRIMESTER II DAN III DI PUSKESMAS AMURANG TIMUR - Tampinongkol, Melchy W.; Mayulu, N.; Kawengian, S. (Pascasarjana Unsrat, 2013)
Maternal mortalityin developing countries according to the WHO (World Health Organisation) 40% associated with anemia inpregnancy. Maternel Mortality Rate (MMR) is one indicator ofthe success of health careina country, It is associated with the occurrence of anemia include sufficient levels of vitamin C andiron sufficiency level. The purposeof this study to determine the relationship of the consumption of protein, B vitamins, filicacidand iron with the incidence of anemia in pregrant women in the second and third trimester Amurang Health Center East. Types of analytic studies is the cross sectional study design. The experiment was conductedat the health centerwith a sample of East Amurang Pregnant women with gestational age Trimester II and III. The research instrument used in this study is the questioner Semi Quantitative Food Frequency (FFQ) and blood laboratory test method Cyanmethemoglobin. Statistical analysis used the chi squeare test. Results of data analysis of protein consumption relationship with the incidence of anemia using Chi-Square test vaues obtained Ï=0.000, using the error rate Î±=0.05 so the value of Ï=0.000>0.05, the relationship of vitamin C with anemia with a value of Ï=0.000<0.05, the relationship with the consumption of folic acid anemia with Ï value=0.000<0, the relationship with the consumption of iron anemia with Ï value=0.000<0.05 anemia.